Corporate Governance Dan Pengungkapan Corporate Social Responsibility Pada Perusahaan Go-Public Di Bursa Efek Indonesia - I Made Sudana; Putu Ayu Arlindania (Jurnal Manajemen Teori dan Terapan | Journal of Theory and Applied Management, 2011)
This research investigates the influence of corporate governance toward corporate responsibility disclosure. This research using the proxy of women representation on board, existence of foreign nationalities on board, size of board of independent commissioner as the variable of corporate governance and size, ROE, DER as control variable. The corporate social responsibility disclosure include details of the environment, energy, employee health and safety, employee other, products, community involvement, and general. The sample of this research was extracted with purposive sampling method. The population is the companies listed at Indonesia Stock Exchange. The technique for examining hypothesis is multiple regression analysis. The results indicate that woman on board and DER have a negative non significant effect to corporate social responsibility disclosure. Existence of foreign nationalities on board, size of board of commissioner, size and ROE have a positive significant effect to corporate social responsibility disclosure.